2014
DOI: 10.1002/lary.24913
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hearing loss in South Korea: Data from a population-based study

Abstract: The prevalence of hearing loss in South Korea was higher in men and older participants according to the data collected from the KNHANES. The patterns of hearing loss differed between hearing loss at speech-relevant frequencies and at high frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 21 publications
1
38
1
2
Order By: Relevance
“…This difference can be explained partially by the fact that we excluded any participants with abnormal tympanic membrane in this study. A recent KHANES study of the same period showed that the prevalence of hearing loss in Korean population was 22.7%, when tympanic membrane abnormalities were included [17]. Similarly, recent work has demonstrated that 20.3% of Americans 12 years and older have hearing loss (NHANES 2001–2008) [16].…”
Section: Discussionmentioning
confidence: 99%
“…This difference can be explained partially by the fact that we excluded any participants with abnormal tympanic membrane in this study. A recent KHANES study of the same period showed that the prevalence of hearing loss in Korean population was 22.7%, when tympanic membrane abnormalities were included [17]. Similarly, recent work has demonstrated that 20.3% of Americans 12 years and older have hearing loss (NHANES 2001–2008) [16].…”
Section: Discussionmentioning
confidence: 99%
“…In another subgroup analysis, we grouped participants according to income level (low income [14], middle income [58], and high income [911]). Two-tailed analyses were conducted, and P values less than 0.05 were considered to indicate significance.…”
Section: Methodsmentioning
confidence: 99%
“…Hearing impairment is one of the most common disorders, with prevalences of 22.73% and 21.7% in the general Korean and US populations, respectively [1,2]. In addition, 9.2% of Korean adults showed moderate-to-profound hearing impairment [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that two-thirds of individuals over the age of 70 years in the United States have a hearing impairment [2]. Similarly, it has been estimated that 84.9% of Koreans aged 80 years or older exhibit bilateral hearing impairment, while approximately 6% of the young individuals (younger than 50 years of age) presents bilateral hearing impairment [3]. Due to the high prevalence of hearing impairment, the proper interpretation of self-reported hearing loss is crucial for predicting audiometric hearing loss.…”
Section: Introductionmentioning
confidence: 99%